Middle school mathematics teachers' orientations and noticing of features of mathematics curriculum materials. (2018) - Roth McDuffie, Amy; Choppin, Jeffrey; Drake, Corey; Davis, Jon
Highlights: Teachers attended to similar features and recommendations of teacher resources. Most teachers planned lesson based on their perspectives on instruction. Most teachers' perspectives on instruction aligned with curriculum they used. Most teachers who planned with an unfamiliar curriculum substantially adapted it. Implications for curriculum developers, policy makers, and educators are presented. Abstract: We report findings on teachers' noticing of features in the teacher resources of mathematics curriculum programs. Based on prior analysis, we selected teachers using one of two curriculum types: delivery mechanism or thinking device. The participating teachers and the curriculum programs aimed to align with the Common Core Standards for Mathematics, and thus, they ostensibly held a common aim for instruction. We analyzed 147 lesson planning interviews with 20 middle school mathematics teachers. We found that teachers attended to similar features of teacher resources; however, patterns for interpreting and planning decisions varied based on teachers' orientations and curriculum type.